2023
DOI: 10.1186/s41043-023-00410-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of triglycerides to high-density lipoprotein cholesterol and triglyceride glycemic index for diabetes incidence in pre-diabetes patients: a prospective cohort study

Abstract: Background The triglyceride glucose (TyG) and triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-c) are the indices that can predict the progression of pre-diabetes to type 2 diabetes mellitus (T2DM). This study aimed to examine the relationship between TyG and TG/HDL-c indices with the incidence of T2DM in pre-diabetes patients. Methods A total of 758 pre-diabetic patients aged 35–70 years who were enrolled in a prospective Fasa Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Independently, a recent prospective study demonstrated a clear relationship between elevated TG/HDL levels (as well as elevated triglyceride/glucose index) and insulin resistance as a predictor of progression from prediabetes to diabetes. 29 This finding is of value because a meta-analysis indicated the high frequency of new-onset diabetes in long-COVID-19 patients, with risks ranging from 11% to 276% compared with patients. 30 Further research is needed to explain why only 3.5% of all potential patients with a potential worsening insulin resistance after COVID-19 develop IST.…”
Section: Discussionmentioning
confidence: 96%
“…Independently, a recent prospective study demonstrated a clear relationship between elevated TG/HDL levels (as well as elevated triglyceride/glucose index) and insulin resistance as a predictor of progression from prediabetes to diabetes. 29 This finding is of value because a meta-analysis indicated the high frequency of new-onset diabetes in long-COVID-19 patients, with risks ranging from 11% to 276% compared with patients. 30 Further research is needed to explain why only 3.5% of all potential patients with a potential worsening insulin resistance after COVID-19 develop IST.…”
Section: Discussionmentioning
confidence: 96%